1969
DOI: 10.1001/archpedi.1969.02100040866009
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Orotic Aciduria With Normal Growth and Development

Abstract: Hereditary orotic aciduria was found in a 7-year-old girl who had anemia, leukopenia, a megaloblastic bone marrow, crystalluria, and normal growth and intelligence. Uridine produced a rapid hematologic improvement, similar to that seen in the previously reported cases. The 24-hour excretion of urinary orotic acid ranged from 290 mg while the patient was on a dosage of 150 mg/kg/day of uridine, to 650 mg while she was on a dosage of 20 mg/ kg/day. The urinary orotic acid/creatinine ratio varied inversely with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Of nine subjects with OA, two were found to have decreased OPRTase and OMPdecase enzyme activities, which were also documented in a parent of each child. Early reports of children with OA without megaloblastic anemia, abnormal growth, or developmental delay (Tubergen et al 1969) may well represent UMPS -mutation carriers, as they were reported in the pre-molecular age.…”
Section: Discussionmentioning
confidence: 97%
“…Of nine subjects with OA, two were found to have decreased OPRTase and OMPdecase enzyme activities, which were also documented in a parent of each child. Early reports of children with OA without megaloblastic anemia, abnormal growth, or developmental delay (Tubergen et al 1969) may well represent UMPS -mutation carriers, as they were reported in the pre-molecular age.…”
Section: Discussionmentioning
confidence: 97%
“…Orotic acid-6-14C (43.5 mCi/mmole), orotic acid-7-uC (8.3 mCi/mmole), orotidine-5'-monophosphate-7-14C (21 FIGURE 1 The reactions involved in the conversion of orotic acid to uridine-5'-monophosphate which are catalyzed by orotate phosphoribosyltransferase and orotidylic decarboxylase.…”
Section: Methodsmentioning
confidence: 99%
“…Incubation of intact erythrocytes in the presence of 1 mm orotic acid (two experiments) or 1 mM orotidine (one experiment) Effect of allopurinol on pyrimidine metabolism in patients with orotic aciduria. Two children with hereditary orotic aciduria (21,22) were treated for 8 wk with allopurinol, 6-8 mg/kg per day (Table V) (24) have proposed a molecular model to explain drug effect, tolerance, and withdrawal in which drug-mediated inhibition of an enzyme is followed by increased levels of the inhibited enzyme. This increase in enzyme activity would result in the need for larger amounts of drug to effect the same response.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, subtype III, resulting also from a biochemical defect in ODC, has been reported in only 2 cases, which presented with orotic aciduria but without megaloblastic anemia (OAWA). Since the report of these cases was prior to the molecular era, these two cases may be simply carriers for the disease ( Tubergen et al, 1969 ; Bailey, 2009 ; Wortmann et al, 2017 ). In addition, heterozygosity for UMPS variants was recently found to be associated with mild asymptomatic orotic aciduria [OMIM#258900] ( Robinson et al, 1984 ; Wortmann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%